On the electric dipole moment of the electron and the P,T-odd electron-nucleus interaction in highly-charged heavy ions - Bondarevskaya, Anastasia A.; Chubukov, D. V.; Andreev, O. Yu; Mistonova, E. A.; Labzowsky, L. N.; Plunien, G.; Liesen, Heinz-Dieter; Bosch, F. (Journal of physics. B, Atomic, molecular and optical physics, 2015)
It is demonstrated that the effect of the electric dipole moment of electron and of the P,T-odd electron-nucleus interaction can be well distinguished in the experiments with H-like (or Li-like) highly charged ions in storage rings. These two effects cannot be separated in the experiments with a certain atom or molecule. Possible experiments for the search of P,T-odd effects with H-like ions in storage rings are discussed and the parameters of these experiments (observation time, field control) are estimated.